My brand, our festival - Exploring the impact of self-image congruency on loyalty in case of music festivals - Kazár, Klára; Prónay, Szabolcs (Marketing & Menedzsment, 2017)
THE AIMS OF THE PAPER We examine music festivals in our study, which can be considered one of the most important community building events nowadays. In our research, we examined how music festival loyalty is explained by self-concept congruency (1) and by psychological sense of a brand community (2). Based on our assumptions, music festival loyalty is stronger if there is a congruency between someone’s self-concept and between the image of the festival (or the visitors of the festival). Moreover, a sense of connectedness with other festival visitors can also strengthen loyalty. METHODOLOGY A questionnaire survey was conducted in 2015 in the area of a popular music festival, the Youth Days of Szeged (SZIN). In the course of the survey, 707 responses were collected, and a PLS path analysis was applied to study the relationships between the concepts included in the research question. MOST IMPORTANT RESULTS Results show that self-image congruency affects the psychological sense of brand community, as well as attitudinal and behavioural loyalty; while the psychological sense of brand community has a significant impact only on attitudinal loyalty. On the basis of the model, the following impact chain (dominant path) is identified: self-image congruency - the psychological sense of brand community - attitudinal loyalty behavioural loyalty. This can be interpreted as: an individual willingly identifies with a group similar to them, shows greater commitment to an event visited by this group, and thus more likely to return. Another interesting finding is that self-image congruency had a significant positive effect on each element of the model, so this is a key factor concerning festival-loyalty. RECOMMENDATIONS The results also draws the festival organizers’ attention to that, besides arranging a high-quality programme, it should also be a priority to build a brand personality congruent with the self-image of the target group.